Diverted to Delhi - Stitt, Greg; Australian Film Finance Corporation (New York, NY : Filmakers library, 2002)
The toll-free telephone numbers used to place orders are often answered thousands of miles away by Indians trained to speak and think like Americans, or Brits or Australians. This film follows a group of university graduates through a rigorous 3-week course which they hope will prepare them for prestigious, well paying positions in these call centers. Over 200 of the U.S. Fortune 500 companies now choose to service their clients via Indian call centers where labor and set-up costs are low and the staff highly educated
Title from title screen
Developed in association with the Australian Film Commission ; produced with the assistance of the Australian Broadcasting Corporation
Executive producer, Dasha Ross ; camera, Joel Peterson ; editor, Fiona Strain
Narrator: Tiriel Mora
Commentary: Kiran Karnik, Ravi Sikund, Ian Stern, Padmini Misra, Jacqueline Armitage, Phil Ashley, Paul Sanderson, Raman Roy
DVD format
Keywords: North Star Call Centre College (Delhi : India); Call centers -- India; Call centers -- Employees -- Training of; Telephone answering services -- India; Telephone answering services -- Employees -- Training of; International business enterprises -- Subcontracting